Convergence of Sharia Maqashid and Environmental, Social, and Governance (ESG) in Sustainable Sharia Economic Development - Moh. Najiburrahman; Siti Wasilah (CV Edujavare Publishing, 2026)
The emergence of the Environmental, Social, and Governance (ESG) framework has established a new paradigm for achieving sustainable economic development. Meanwhile, Islamic economics possesses a strong normative foundation through the principles of Maqashid Sharia, which emphasize the realization of public welfare (maslahah). However, studies integrating these two frameworks remain limited, resulting in the absence of a comprehensive conceptual model that explains the relationship between ESG indicators and the objectives of Maqashid Sharia in contemporary Islamic economics. This study aims to analyze the convergence between ESG principles and the dimensions of Maqashid Sharia while formulating a conceptual framework for sustainable Islamic economic development. This research employs a normative legal research method using a conceptual approach and library research. The data were collected from the Qur'an, Hadith, classical and contemporary literature on Maqashid Sharia, regulations concerning sustainable finance, and relevant national and international scholarly publications. The collected data were analyzed using descriptive-analytical methods. The findings reveal that ESG principles substantially align with the five essential objectives of Maqashid Sharia (hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, and hifz al-mal). The environmental dimension reflects sustainability in preserving ecological welfare, the social dimension promotes justice, human rights protection, and social prosperity, while the governance dimension reinforces trustworthiness, transparency, accountability, and justice within Islamic economic activities. This study proposes a conceptual model integrating ESG with Maqashid Sharia as a new paradigm for strengthening the competitiveness, sustainability, and global legitimacy of the Islamic economic system.